Pelatihan Menghafal Al-Qur’an Dengan Metode Ritme Otak Kanan bagi Santri Pondok Pesantren Muhammadiyah Darul Hikmah - Iswati Iswati; Diah Novita Fardani; Heri Cahyono; Syaiful Anam (CV. Creative Tugu Pena, 2021)
Using method in memorizing Al Qur’an was the most important element in teaching. The memorization of Al Qur’an method that has long been used was the tahfidz and tikrar methods. Ideally, the method of tahfidz and takrir should be continuous, but students often forget to repeat their memorization because they were complacent about the amount of memorization they have gotten. This article aimed to accompaniment the students in training memorize the Qur'an with the rhythm method of the brain. This research used participation action research (PAR), through analysis survey and the implementation of counseling and training.The result show that Memorizing Al-Qur’an with the Rhythm Brain method, which is a way to memorize the Al-Qur’an by exerting all five senses, be it hand movements, head, vision, hearing, and mind that focus on memorizing the Al-Quran marked by using letter symbols and numeric codes accompanied by rhythm (the tone of sound when pronouncing a sentence in the Koran) so that it is easily stored in the right brain and imagined (imagined) for long-term memory. Students have an alternative method of memorizing that is fun, more effective and makes it easier for students. So that the motivation to memorize was maintained and the memorization target was achieved. Keywords: Memorizing Al Qur’an, Training of Memorizing Al Qur’an, Tahfidz